Vegetation Function Analysis in Musamus University Campus Area - Maichel Santo W. Mita; Atiza Nurhuzna; Yohannes Putra P. Sinambela; Reivandi Christal Joenso (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The academic community’s point of activity, the campus area, requires green open spaces to support its activities. The Musamus University campus area boasts 27 different types of scattered plants. A qualitative methodology was employed to identify the types and functions of vegetation in the Musamus University campus area, including data collection, vegetation mapping, diversity analysis, function identification, and data analysis. The research revealed that the Musamus campus area lacks vegetation, particularly in terms of shading, aesthetic, and guiding functions, although it does serve well as a noise dampener. Therefore, there is a need to increase the quantity of vegetation, especially those that provide shading, aesthetic, and guiding functions.